Self-repair in EFL learners' speech in two contrasting institutional school settings in China: An activity theory informed analysis. (April 2022) - Zeng, Simin; Evans, Michael
Abstract: This article uses activity theory to consider how L2 learners' self-repair behaviour takes shape in their situated learning contexts. It compares and investigates EFL learners from two secondary schools in China that differed in their L2 pedagogical systems and overall educational cultures: a mainstream public school and a private school that provides an international curriculum. Data from classroom interactions, lesson observations and interviews with teachers and students were triangulated. Analysis of data reveals that tension or affordance could arise out of the interaction within or between different constituents of an activity system of a school setting. This exerts further mediating influences on L2 learners' self-repair behaviour, including the frequencies, underlying problems, strategies used and changes incurred. This paper concludes by suggesting that EFL practitioners should be more mindful of students' self-repair features in order to reflect on possible sources of tension that can stem from different elements of an activity system, to consider potential forms of conflict resolution, and to create an environment that is conducive for the creation of affordances for learning. Further research using activity theoretical reconceptualization and the concept of expansive learning is called for.